Screening and Identification of a Chicken Dendritic Cell Binding Peptide by Using a Phage Display Library - Ma, Sunting; Qiao, Xinyuan; Xu, Yigang; Wang, Li; Zhou, Han; Jiang, Yanping; Cui, Wen; Huang, Xuewei; Wang, Xiaona; Tang, Lijie; Li, Yijing (Frontiers in Immunology, 2019)
Dendritic cells (DCs), as antigen-presenting cells, can initiate adaptive immune responses efficiently. Although the DC-targeting strategy has attracted more attention, relevant studies on chicken are rare. Here, specific chicken bone marrow DC-binding peptides were selected using a phage display peptide library and confirmed through ELISA, flow cytometry, fluorescence microscopy, and laser confocal microscopy. The peptide candidate SPHLHTSSPWER, named SP, was fused to the infectious bursal disease virus (IBDV) structural protein and protective antigen VP2. In vitro, the expression of DC markers (CD80, CD83, CD86, DEC205, and MHCⅡ) and some cytokines (IFN-γ, IL-12, TNF-α, IL-1β, IL-6, and CXCLi1) by VP2-SP-stimulated DCs was significantly higher than that by DCs treated with the VP2-control peptide at 4 h (p ＜ 0.001). In addition, an oral vaccine targeting DCs was generated using chicken-borne Lactobacillus saerimneri M11 (L. sae M11) to deliver VP2 fused with SP. Anti-IBDV mucosal and humoral immune responses were induced efficiently via oral administration, resulting in higher protective efficacy in the VP2-SP group than the VP2 group. Therefore, chicken DC targeting of IBDV protective antigen VP2 delivered by L. sae provides effective immune protection in chicken. Our study may promote research on the DC-targeting strategy to enhance the effectiveness of chicken vaccines.